(untitled) (GEON Journal (Management, Organizations and Business), 2023)
Problematic. The proper functioning of organizations depends on the performance of their employees. Their perception of well-being and the organizational climate are a determining factor in cultivating productivity. Studying these aspects is relevant to avoid staff turnover and to set long-term objectives. objectives. General: To characterize the organizational climate and labor welfare of the commercial advisors of the company Ktronix Unicentro Bogotá. Specific. To analyze the job satisfaction of the commercial consultants. Determine the employees’ perception of well-being. To establish the structure of the work team of this commercial area. materials and methods. It is based on a quantitative approach with a descriptive-explanatory scope. A survey-type questionnaire was applied to a sample of 55 individuals equivalent to the total population. Descriptive analysis is performed in order to explore the data, discover patterns or trends by determining the levels of job satisfaction, motivation, structure of the work team and outstanding features in the data found. Results. It highlights the favorable satisfaction on the part of the personnel, finding explanatory discrepancies according to seniority in the organization, age and position held. Discussion. Studies of this type need to be put in context, avoiding generalizations, since there are cultural, socio-political and economic characteristics that condition the perception of well-being and the work climate in organizations. Conclusions. This research allows us to conclude that the perception of well-being and work environment is a niche element, which denotes specific characteristics that are explained by the context that gives meaning to the results obtained. Contribution / originality. Particular traits are evidenced in collaborators of a technology commercialization company, allowing to know that the perception of well-being does not depend on the position or salary range, but obeys to particular conditions of each organization and its collaborators, demonstrating the need to carry out studies in a particular way that avoids abstract generalizations.